Evaluation of Current Environment Status of Kottayam Chira - Rakesh V.B., Adhem Shahin, Amarnath A. and Rojith G. (International Research Journal of Environment Sciences, 2013)
Kottayam Chira is a significant water body with a total area of around 11 acres at present. It is located about 1.5 kms away from Kuthuparamba town of Kannur district, northern part of the ‘State of Kerala’. The coordinates of the study area 11 0 49′ N and 75 0 33′ E. The Kottayam chira is environmentally, historically and culturally of no match and is of utmost significance. Additionally it was part of the livelihood of the native population as it acted as reservoir to supply water for irrigation into the adjoining paddy fields and also people were dependent on it for its fish wealth. This significant wetland is now in an environmentally neglected and degraded form mainly due to eutrophication, weeding, siltation, etc. Due to excessive siltation it is seen that stagnant pools have formed in the water body; this may act as a threat zone to yield various water borne disease. This study deals with the estimation of essential water quality parameters of the study area. The various parameters were calibrated and it is compared with the international standards. The obtained values were matched with WHO drinking water standards and ISO standards. The study revealed that due to the neglected state of the Chira, various parameters are far beyond permissible limits. It is a clearcut example of how anthropogenic over-exploitation and negligence can deteriorate a well-established ancient aquatic ecosystem.